Creatinine‐based equations for the adjustment of drug dosage in an obese population. (17th January 2016) - Bouquegneau, Antoine; Vidal‐Petiot, Emmanuelle; Moranne, Olivier; Mariat, Christophe; Boffa, Jean‐Jacques; Vrtovsnik, François; Scheen, André‐Jean; Krzesinski, Jean‐Marie; Flamant, Martin; Delanaye, Pierre
Abstract : Aim: For drug dosing adaptation, the Kidney Disease: Improving Global Outcomes (KDIGO) guidelines recommend using estimated glomerular filtration rate (eGFR) by the Chronic Kidney Disease Epidemiology Collaboration (CKD‐EPI) equation, after 'de‐indexation' by body surface area (BSA). In pharmacology, the Cockcroft–Gault (CG) equation is still recommended to adapt drug dosage. In the context of obesity, adjusted ideal body weight (AIBW) is sometimes preferred to actual body weight (ABW) for the CG equation. The aim of the present study was to compare the performance of the different GFR‐estimating equations, non‐indexed or de‐indexed by BSA for the purpose of drug‐dosage adaptation in obese patients. Methods: We analysed data from patients with a body mass index (BMI) higher than 30 kg m −2 who underwent a GFR measurement. eGFR was calculated using the CKD‐EPI and Modification of Diet in Renal Disease (MDRD) equations, de‐indexed by BSA, and the CG equation, using either ABW, AIBW or lean body weight (LBW) for the weight variable and compared with measured GFR, expressed in ml min −1 . Results: In our population of obese patients, use of the AIBW instead of the ABW in the CG equation, markedly improved the overall accuracy of this equation [57% for CGABW and 79% for CGAIBW ( P  < 0.05)]. For high BMI (over 40 kg m −2 ), the accuracy of the CG equations is no different when using LBW than when using AIBW. The MDRD and CKD‐EPI equations de‐indexed by the BSA also performed well, with an overall higher accuracy for the MDRD de‐indexed equation [(80% and 76%, respectively ( P  < 0.05)]. Conclusions: The de‐indexed MDRD equation appeared to be the most suitable for estimating the non‐indexed GFR for the purpose of drug dosage adaptation in obese patients.